ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN ANAK TUNAGRAHITA RINGAN PADA SISWA KELAS VII-C DI SLB NEGERI 1 SINJAI KECAMATAN SINJAI UTARA - Srimularahmah, Andi; Buhari, Sarni (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Sarni Buhari, NIM 317052. Analysis of Reading Comprehension of Mild Mentally Impaired Children in Class VII-C SLB Negeri 1 Sinjai, North Sinjai District.In the Indonesian Language Education Study Program.Faculty of Teacher Training and Education.Muhammadiyah University of Bone.The study describes the reading comprehension ability of grade VII-C students at SLB Negeri 1 Sinjai, North Sinjai District in the aspect of reading discourse.The method used in this research is descriptive method.In accordance with field observations, the researchers described that the reading ability of grade VII-C students at SLB Negeri 1 Sinjai, North Sinjai District, amounted to 7 students, with the number of male students being 2, and the number of female students being 5 students.And 2 students who are able to read fluently and precisely, in the good category assessment.